Uncovering sophisticated discrimination with the help of credence goods markups: Evidence from a natural field experiment - Jonathan Hall; Rudolf Kerschbamer; Daniel Neururer; Eric Skoog (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We present the results of a pre-registered natural field experiment designed to uncover a sophisticated form of discrimination against an immigrant minority in a market for credence goods. For this purpose, we introduce two markups: (i) the credence goods markup defined as the difference between the price paid by the same person for an ordinary service and an otherwise equivalent credence goods service; and (ii) the discriminatory markup defined as the difference between the price paid by a member of an immigrant minority group and the price paid by a member of the majority group for the same kind of service. We document the existence of a large credence goods markup of about 40%, on average. Moreover, we find a sizeable discriminatory markup for the credence goods service but no discriminatory markup for the ordinary service. The results of an ex-post survey suggest that this sophisticated form of discrimination is mainly due to the prejudicial behavior of sellers belonging to an established local ethnic minority group towards buyers belonging to a low-status immigrant ethnic minority group.
Keywords: C93; D82; J15; 330; natural field experiment; credence goods; discrimination; expert services; credence goods markup; discriminatory markup